2009 16th IEEE International Conference on Image Processing (ICIP) 2009
DOI: 10.1109/icip.2009.5413857
|View full text |Cite
|
Sign up to set email alerts
|

Directional wavelet transforms for prediction residuals in video coding

Abstract: Various directional transforms have been developed recently to improve image compression. In video compression, however, prediction residuals of image intensities, such as the motion compensation residual or the resolution enhancement residual, are transformed. The applicability of the directional transforms on prediction residuals have not been carefully investigated. In this paper, we brie y discuss differing characteristics of prediction residuals and images, and propose directional transforms speci cally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 8 publications
(15 reference statements)
1
34
0
5
Order By: Relevance
“…However, we note that the number of possible combinations is the number of transforms to the power of the number of blocks, which is very large even for the simplest case of two transforms. Some recent studies [2] have considered a set of as many as 17 different transforms that can be (a) A typical image chosen for each block. This implies that brute force method is not practical.…”
Section: Transform Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we note that the number of possible combinations is the number of transforms to the power of the number of blocks, which is very large even for the simplest case of two transforms. Some recent studies [2] have considered a set of as many as 17 different transforms that can be (a) A typical image chosen for each block. This implies that brute force method is not practical.…”
Section: Transform Environmentmentioning
confidence: 99%
“…Recently, it has been observed that the statistics of motion-compensated residuals is different from that of typical images. Specifically, the work in [2] reports that the correlation of motion-compensated residuals can be better characterized as: By comparing the rate-distortion performance of three different settings, it is reported that for typical video sequences, much bit saving is due to the use of only vertical and horizontal 1D-DCTs.…”
Section: Direction-adaptive 1d Dctsmentioning
confidence: 99%
See 3 more Smart Citations